Teacher ambivalence towards school evaluation: promoting and ruining teacher professionalism. Issue 3 (1st January 2016) - Hult, Agneta; Edström, Charlotta
Abstract : Today's evaluation society makes teachers participate in a stream of external evaluations. How teachers experience evaluation in school and how this affects their work and professionalism is the focus of this article. Teachers' views of external and internal evaluations and of the consequences for school practice are described and analysed. The interviewed teachers emphasised the importance of internal evaluations performed close to daily teaching practice and jointly with students and colleagues. These evaluations are generally overlooked in evaluation and school-policy research and seldom attended to or appreciated by school providers. Further, teachers were critical of and reported several negative consequences of accountability and external evaluations, but still generally complied by participating in them. The present results are discussed in relation to professional responsibility and accountability as well as to possible constitutive effects. By emphasising that their daily informal evaluations represent their efforts to improve teaching, teachers are describing parts of their professional responsibility. However, the negative consequences of external evaluations signal constitutive effects on teachers' work, described as making it less creative, discretionary and autonomous as well as increasing mistrust, meaning that more tests are required in order to legitimate student grades.